2022
DOI: 10.3390/ijms23105814
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Patients with Insulin Resistance: Etiopathogenesis and Management in Children

Abstract: Insulin resistance (IR) is a key component in the etiopathogenesis of hypertension (HS) in patients with diabetes mellitus (DM). Several pathways have been found to be involved in this mechanism in recent literature. For the above-mentioned reasons, treatment of HS should be specifically addressed in patients affected by DM. Two relevant recently published guidelines have stressed this concept, giving specific advice in the treatment of HS in children belonging to this group: the European Society of HS guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…Several studies demonstrated an association between arterial hypertension and insulin resistance and this is also a problem for pediatric patients [ 21 ]. Insulin resistance is involved in the development of hypertension through various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated an association between arterial hypertension and insulin resistance and this is also a problem for pediatric patients [ 21 ]. Insulin resistance is involved in the development of hypertension through various mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Excess adipose tissue can increase IR by promoting inflammation through increased levels of resistin or tumour necrosis factor-α. Adipose tissue macrophages activate inflammatory signalling pathways within neighbouring insulin-targeting cells (adipocytes), releasing inflammatory factors directly involved in the development of IR ( 45 ).IR increases the sympathetic nervous system by enhancing angiotensin II (AngII) and aldosterone activity, and oxidative stress leads to elevated blood pressure ( 46 ). Therefore, it is advisable to eat a light diet, reduce the intake of high-fat diets, control body weight and blood glucose, enhance exercise, and regularly monitor fat content, blood glucose, and lipid levels to prevent hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Locally produced IGF-1 supports blood vessel reparation and downregulates inflammation-related oxidative stress [ 2 ]. IGF-1 participates in the regulation of regional blood flow and blood pressure via stimulation of endothelial nitric oxide synthase (eNOS) activity and nitric oxide (NO) production in endothelial cells [ 4 ] that results in the induction of vasodilation and increased blood flow [ 5 ]. Genetic IGF-1 deficiency in mouse models leads to elevated blood pressure, supporting the role of IGF-1 in blood flow and pressure regulation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%